Evaluation of Iso 31000 Risk Implementation in in DKI Jakarta Provincial Government-Owned Enterprises (BUMN) Subsidiaries (Case Study on PT B, A Subsidiary of PTX) - Kautsar, Dzaid Al; Djakman , Chaerul D. (Jurnal Locus Penelitian dan Pengabdian, 2025)
PTX is a regionally-owned enterprise of the Jakarta provincial government operating in the public transportation sector, and PT. B is a subsidiary of PT. X engaged in property development and property management, particularly in the Jakarta area. Since its establishment in 2020, PT. X has not conducted an evaluation regarding the conformity of ISO 31000 implementation in risk management at PT. B. This study aims to evaluate the conformity of risk management at PT. B based on ISO 31000. The research uses a case study approach through document observation, interviews, and literature findings. The results of this study indicate that PT. B is aware of the importance of risk management implementation and has made efforts to apply risk management. However, the implementation of risk management is still not in accordance with the ISO 31000 risk management standard. PT. B does not yet have an integrated system related to risk management implementation. The risk management documentation process is still carried out in a simple manner. The processes of identification, mitigation, monitoring, and evaluation are still focused on top risks. PT. B also does not yet have a dedicated work unit for risk management within the company. It is expected that this research can serve as evaluation material for the company, especially the risk management work unit, so that the implementation of risk management can be maximized in accordance with ISO 31000 standards. Abstracts are written in Indonesian and English, consisting of the main problem, objectives, methods, and research results.